Technology Entrepreneurship : Comb Sprayer / Ameerah Mansor ...[et al.] - Mansor, Ameerah; Abdul Halim, Ashila Husna; Rashif, Noor Aisyah; A Rahman, Rabiatul Adawiyah; Wan Mohd Fauzi, Wan Noradzwa (2019)
Hair care is an overall term for hair treatment involving the process of brushing hair and the usage of hair serum or oil which responsible for maintaining the heath and beauty of hair. Hair care services are offered in salons, barbershop and day spas, and the products are also available commercially for home use. The beauty centre like salon needs the product that can help them to make their work easy and efficient. Therefore, the A's company has produced the comb sprayer in order to solve their problem. However, this product has to complete to the other company that have the same feature of the product. Therefore, the comb spray has come with variety of designs and also functions to attract more consumers. There are also a few problem with the current products in the market in a few aspects. The price and functions is mostly people pointing out as the issue. Comb sprayer with manual function of course comes with affordable price but the function is too simple yet far from being convenient. The one with automatic function, on the other hand, is quite expensive. So most of the people cannot afford it even though the system is really efficient. Comb sprayer has been buit to cater with the problem as it offers an affordable price, convenient and most importantly, it is simple to use.